Effectiveness of Flipchart-Based Education on Premarital Screening Knowledge: A One-Group Pretest-Posttest Study Among Prospective Couples at a Primary Health Center - Ni Putu Yogi Febriyanti Afsari; Ni Nyoman Suindri; Ni Komang Yuni Rahyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2026)
Premarital screening is an important strategy to identify potential health risks before marriage and improve reproductive health outcomes. However, its utilization remains low, partly due to limited knowledge among prospective couples and the suboptimal use of effective educational media such as flipcharts. This study aimed to determine the effectiveness of flipchart-based health education in improving knowledge of premarital screening among prospective couples at UPTD Health Center I, West Denpasar. This study used a pre-experimental one-group pretest–posttest design. A total of 30 respondents (15 couples) were selected using consecutive sampling. Data were collected using a structured questionnaire administered before and after the intervention. The mean knowledge score increased from 62.83 to 90.83. The Wilcoxon signed-rank test showed a significant difference between pretest and posttest scores (p < 0.05), with 29 respondents demonstrating improvement. These findings indicate that the flipchart-based health education is effective in improving premarital screening knowledge. Therefore, the use of visual educational media is recommended to support health education programs in primary health care settings.